Tecnologia aplicada ao direito: os desafios na gestão de dados dos processos eletrônicos e os impactos no desenvolvimento da jurimetria - Esteves, Mariana Aguiar (2021)
The relationship between law and technology has been a topic with growing curiosity and has been disseminated by recent debates involving mainly the electronic process and the legal system in this new universe of data in the Judiciary. Within this area, the focus given to the theme in this work refers to the impacts of the computerization of the Judiciary on access to Justice, on the efficiency and effectiveness of the judicial provision, as well as on the legal professions and services provided by law operators in the order and falls within the research line of the Justice and the Efficiency Paradigm. The objective of this dissertation work is to analyze the technology applied to the Law in these fronts, as well as in the management of the jurisdictional activity and thus to map the challenges that arise and may still arise in the face of this digital evolution, mainly regarding the development of Jurimetry and the massive production of electronic data arising from lawsuits by the various systems used by brazilian courts. The main aspects of the access to Justice and the consequences of the virtualization of processes in this right will be discussed and the transition of the electronic process and its particularities in the Brazilian legal system will also be analyzed. Then, the focus will be on the applicability of jurimetry and artificial intelligence today, facing an exponential production of data, on the relevant role of jurimetry in the field of standardization of national jurisprudence and the challenge for the management of all these data produced at collected, studied and stored by the Judiciary. As the theme is recent, a bibliographic review about it was carried out, using the hypothetical-deductive method, based on bibliographic research, in addition to consulting literature also published in traditional Brazilian and foreign media. It was noticed that there is still a distance and absence of an instrument capable of regulating the management of the data of electronic judicial processes that are of great relevance for the development of jurimetry, but that must be properly protected and managed by the Judiciary, in view of the risks and possible ethical conflicts regarding advertising, privacy and security of this data. In summary, this work points to the importance of monitoring the use of these technological tools in view of the problem that involves the security and publicity of electronic judicial data in the face of the reality of intense and massive judicialization by society, the exponential production of constant and investigating how this will impact efficiency in jurisdictional performance by improving the management of this data from electronic court cases.